Pengembangan Media Pembelajaran Berbasis PowerPoint untuk Meningkatkan Hasil Belajar Gambar Teknik Proyeksi Amerika - Handriaswara, Handriko; Rohman, Shohihatur; Musyono, Ari Dwi Nur Indriawan; Apristia, Lelu Dina; Kriswanto, Kriswanto (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to develop interactive PowerPoint-based learning media for Engineering Drawing, specifically the topic of American Projections, and to determine the feasibility and effectiveness of this media in improving student learning outcomes. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The developed learning media was validated by material experts and media experts, with an assessment of 84% from the material experts (very feasible category) and 75% from the media experts (feasible category). The trial was conducted in class X of Mechanical Drawing at a Vocational High School (SMK), which showed an increase in the average score of student learning outcomes, from 51.67 (pre-test) to 86.67 (post-test). The results of the effectiveness analysis using the N-Gain formula showed a score of 0.71 or 71.46%, which is included in the moderately effective category. Based on these results, it can be concluded that the developed interactive PowerPoint-based learning media is feasible and effective for use in Engineering Drawing learning, specifically for the topic of American Projections. This media also has the potential to increase student engagement and learning outcomes interactively at vocational high schools.